2021
DOI: 10.1155/2021/5208976
|View full text |Cite|
|
Sign up to set email alerts
|

Design and Analysis of Adolescent Physical Health Monitoring System under the Background of Internet of Things and 5G

Abstract: In recent years, with the rapid development of network communication, 5G technology has brought about higher network speed and more communication requirements. Internet of Things technology has been widely used in many fields. Therefore, this paper realizes the physical health monitoring system under the Internet of Things and 5G communication technology to detect the physical health of teenagers in real time. Based on the in-depth analysis of the theoretical research and application status of the healthy Inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The authors propose different strategies to improve this correlation, but there is still much to be explored within these works. [23][24][25][26] WiFi A great variability of works using Wireless Fidelity (WI-Fi) was proposed in the papers, generating a broad set of key terms. In this context, it is possible to find trustworthiness, affordability, efficiency, security, accuracy, etc.…”
Section: Gmentioning
confidence: 99%
“…The authors propose different strategies to improve this correlation, but there is still much to be explored within these works. [23][24][25][26] WiFi A great variability of works using Wireless Fidelity (WI-Fi) was proposed in the papers, generating a broad set of key terms. In this context, it is possible to find trustworthiness, affordability, efficiency, security, accuracy, etc.…”
Section: Gmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%